C-reactive protein response to influenza vaccination predicts cardiovascular disease risk in the Philippines. (2nd January 2020) - McDade, Thomas W.; Borja, Judith B.; Lee, Nanette; Aquino, Celine T.; Barrett, Tyler; Adair, Linda S.; Kuzawa, Christopher W.
ABSTRACT: Inflammation is associated with increased risk for chronic degenerative diseases, as well as age-related functional declines across many systems and tissues. Current understandings of inflammation, aging, and human health are based on studies conducted almost exclusively in high-income nations that rely primarily on baseline measures of chronic inflammation. This analysis investigates the inflammatory response to vaccination as a predictor of cardiovascular disease (CVD) among older women in the Philippines, a lower-middle income nation with rising rates of overweight/obesity and relatively high burdens of infectious disease. Concentrations of C-reactive protein (CRP) were measured at baseline and 72 h following influenza vaccination in 530 women (mean age = 55.2 years). Ankle-brachial index (ABI) – an indicator of peripheral arterial disease and broader CVD risk – was measured approximately three years later. The magnitude of CRP response to vaccination was positively associated with ABI, indicating that a larger inflammatory response predicts lower CVD risk. Baseline CRP was negatively associated with CRP response to vaccination, and was not associated with ABI independently of CRP response. These results suggest that research across ecological settings, and with more dynamic measures of inflammatory response and regulation, may yield important insights into the associations among inflammation, aging, and disease.